A crown of stars - Abé, Shana (Kensington Publishing Corp., 2026)
"In turn of the century England, the Jolivet family lives a charmed existence. Daughter of a wealthy vineyard owner and a French pianist, vivacious Marguerite, the eldest of three, loves spinning stories and entertaining her family's well-connected friends. No one is surprised when she announces, at 18, that she intends to become an actress. Her sister, Inez, a virtuosa violinist, moves to London with her. Soon the two beauties are being celebrated in the highest social circles. Marguerite takes the stage name Rita, and quickly draws the attention of legendary theater producer Charles Frohman. From the West End to Broadway, and then in the new medium of silent film, Rita is known for her "sultry eyes, her mystic smile," and her star burns brighter with every role. While filming in Italy, she's courted by a charismatic aristocrat and Rita feels on the verge of a life even better than her dreams. Inez, meanwhile, has already found love, and travels the world with her adored husband. Yet soon, war is raging across Europe. Rita, in New York for the premiere of Cecil B. DeMille's The Unafraid, receives word from Inez that their brother is about to enlist. Hoping to see him before he departs, Rita books a ticket on the fastest steamer available: the RMS Lusitania. But the ship sails under a British flag, and the German government warns that all such vessels are fair game. Few believe Germany would risk attacking a ship carrying Americans, certainly not one as swift and imposing as the Lusy. Once aboard, Rita is delighted to discover both Charles and her brother-in-law as fellow passengers.The days pass in a haze of parties and pleasurable pursuits, and the comforts of the luxury ocean liner are almost enough to calm Rita's ripples of unease. But as the ship nears Liverpool, every assumption will be tested, and Rita, her family, and the world, will be changed forever by the voyage's infamous and catastrophic end . . ."--Amazon.